Historical dictionary of Ukraine - Katchanovski, Ivan (Historical dictionaries of Europe, 2013)
Although present-day Ukraine has only been in existence for something over two decades, its recorded history reaches much further back for more than a thousand years to Kyivan Rus'. Over that time, it has usually been under control of invaders like the Turks and Tatars, or neighbors like Russia and Poland, and indeed it was part of the Soviet Union until it gained its independence in 1991. Today it is drawn between its huge neighbor to the east and the European Union, and is still struggling to choose its own path... although it remains uncertain of which way to turn. Nonetheless, as one of the largest European states, with considerable economic potential, it is not a place that can be readily overlooked.The problem is, or at least was, where to find information on this huge modern Ukraine, and since 2005 the answer has been the Historical Dictionary of Ukraine in its first edition, and now even more so with this second edition. It now boasts a dictionary section of about 725 entries, these covering the thousand years of history but particularly the recent past, and focusing on significant persons, places and events, political parties and institutions as well as more broadly international relations, the economy, society and culture. The chronology permits readers to follow this history and the introduction is there to make sense of it. It also features the most extensive and up-to-date bibliography of English-language writing on Ukraine.